2009
DOI: 10.1016/j.nuclphysb.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Phantom evolution in power-law potentials

Abstract: We investigate phantom models with power-law potentials and we extract the early-time, "tracker", solutions under the assumption of matter domination. Contrary to quintessence case, we find that energy positivity requires normal power-law potentials instead of inverse power-law ones, with the potential exponent being bounded by the quadratic form. In addition, we analytically present the general cosmological solution at intermediate times, that is at low redshifts, which is the period of the transition from ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…This shows that for uncoupling and coupling exponential potentials the evolutions of our universe are very similar in the time interval we consider here. The lower figure is different from Fig.6 but has a common characteristic with the phantom with power-law potential [148], quintessence with inverse power-law potential and Chaplygin gas model [149] that it reaches the point of LCDM with the increasing of time. This is due to the fact that they all lead to the same fate of the universe-de Sitter expansion, but the trajectories to LCDM are different, therefore they can be differentiated.…”
Section: State-finder Diagnosismentioning
confidence: 72%
See 1 more Smart Citation
“…This shows that for uncoupling and coupling exponential potentials the evolutions of our universe are very similar in the time interval we consider here. The lower figure is different from Fig.6 but has a common characteristic with the phantom with power-law potential [148], quintessence with inverse power-law potential and Chaplygin gas model [149] that it reaches the point of LCDM with the increasing of time. This is due to the fact that they all lead to the same fate of the universe-de Sitter expansion, but the trajectories to LCDM are different, therefore they can be differentiated.…”
Section: State-finder Diagnosismentioning
confidence: 72%
“…Firstly we assume that there is no direct coupling between the phantom scalar field and the normal scalar field, that is we assume the simple exponential potentials of the previous subsection: V (σ, φ) = V σ 0 e −ασ + V φ 0 e −βφ , where α and β are constants. As we have shown, in this case the universe is moving towards the phantom dominated, late time attractor [81,82,137,148]. In Fig.6 it is depicted the time evolution of statefinder pair {r, s} in the time interval ∈ [0.…”
Section: State-finder Diagnosismentioning
confidence: 90%
“…Alternative models of dark energy suggest a dynamical form of dark energy, which at least in an effective level, can originate from a variable cosmological constant [24,25], or from various fields, such as a canonical scalar field [26][27][28][29][30] (quintessence), a phantom field [31][32][33][34][35][36][37][38] or the quintom [39][40][41][42][43][44][45][46][47][48][49][50][51]. By using some basic of quantum gravitational principles, we can formulate several other models for dark energy and in literature they are known as holographic dark energy paradigm [52][53][54][55][56][57][58][59][60][61][62][63] and agegraphic dark energy models [64][65][66].…”
Section: Tachyonic Fluidmentioning
confidence: 99%
“…This can be achieved by adding to the matter sector a canonical scalar field [10][11][12][13][14][15][16][17][18][19][20][21][22][23], known as quintessence, a phantom scalar field [24][25][26][27][28][29], or a combination of both of these fields called quintom [30][31][32][33][34][35][36][37][38][39]. A review of these models can be found in [40,41].…”
Section: Introductionmentioning
confidence: 99%